Screening for phosphate-solubilizing fungi from colombian andisols cultivated with coffee (Coffea arabica L.) - González, Hernán; Góngora, Carmenza Esther; Medina, Rubén Darío; Osorio, Nelson Wálter (Coffee Science - ISSN 1984-3909, 2020)
Phosphate (P) bioavailability is severely constrained in volcanic ash soils due to its high fixation rate. To overcome this problem the use of P-solubilizing fungi (PSF) has been proposed gaining recently great attention. However, despite encouraging results in the laboratory, their effectiveness under field conditions is debatable. To provide a better understanding of the dynamics of PSF in soils and to establish criteria for screening effective PSF a series of studies were conducted. PSF were isolated from coffee plantations grown in a Typic Udivitrand (QU), a Pachic Fulvundand (CH), and a Typic Melanudand (Ti). Fifty-four isolates (27 from CH, 19 from Ti, and 8 from QU) produced index of P solubilization among 16 and 106 mg L-1 using as P source phosphate rock. The results suggest that the microbial P solubilization was not only associated to the decrease in the culture medium pH, but also the production of organic acids associated with the most effective PSF. The higher production of organic acids seems to be associated lower fungal colony growth rate likely due to a carbon/energy drainage. The soil P-fixation capacity, soil organic content and degree of humification seems to control the relative abundance of PSF in the soils tested. In soils cultivated with coffee Phlebia subserialis is reported, for the first time, as a PSF. Key words: Colombian coffee zone; soil fertility; phosphorus fixation; organic acids; humificaction degree; Phlebia.